The Relationship Between Proteinuria in Severe Preeclampsia and Maternal and Fetal Outcomes - Parlakgümüş, Huriye Ayşe; Şimşek, Erhan; Çok, Tayfun; Tarım, Ebru (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: To investigate if the degree of proteinuria is related to adverse pregnancy outcomes in preeclampsia patients. STUDY DESIGN: The records of 129 severe preeclampsia, 11 eclampsia and 21 HELLP patients delivered before the 37th gestational weeks in Baskent University Adana Research Center between December 2005 and December 2011 were reviewed retrospectively. Group I (n=118) had proteinuria of less than 5g /24 h and Group II (n=43) had proteinuria equal to or more than 5 g /24 hour. Data were analyzed with Student’s t test, Chi-square test and correlations were made with Pearson correlation test. P<0.05 was considered statistically significant. SPSS for Windows (version 17.0; SPSS, Inc., Chicago, IL) was used for statistical analyses. RESULTS: The patients in group II were significantly younger (30.6±6.27 vs. 27.9±6.25) (p=0.01) and delivered significantly earlier (33.6±3.9 vs. 32±3.3) (p=0.02). Group I patients had significantly more risk factors (16.9 vs. 2.3%) (p= 0.015). History of hypertension was also more common in group I (11 vs. 0%) (p= 0.023). CONCLUSION: The patients with proteinuria of ≥ 5 g/24 hr were younger, delivered at an earlier gestational age and had risk factors less frequently.